(untitled) (Iranian Journal of Kidney Diseases, 2023)
Introduction. With the development of information technology in medical treatment, mobile medical treatment has become a new way to seek treatment, follow-up, extended care, popular science, disease prevention and access to disease expertise. The application of mobile medical treatment is relatively mature in the management of chronic diseases. Currently, mobile medical intervention is also introduced in the self-management of patients after Renal Transplantation. Compared with traditional intervention methods, mobile medical treatment has the advantages of convenience, speed, low cost and no geographical restriction, and it is easy to be used by KT recipients in self-management and has good feasibility. Therefore, we conducted self-management intervention for patients after Renal Transplantation based on mobile medical procedures, so as to improve patients’ satisfaction, medication compliance, follow-up rate, and ease patients’ anxiety about the disease. Methods. A total of 160 discharged patients with stable recovery of transplanted Renal function who underwent renal transplantation surgery in our hospital from January 2021 to January 2023 were selected for retrospective analysis. According to the different intervention plan, the patients were divided into the intervention group and the comparison group, 80 cases each. Among them, the intervention group used the mobile medical application selfmanagement behavior intervention, and the comparison group used the conventional self-management behavior intervention. The differences of self-management behavior score, quality of life score, Basel score and anxiety score between the two groups of patients after Renal Transplantation were analyzed and compared. Results. After intervention, there were statistically significant differences in the scores of self-management behavior scale, Quality of life related rating scale, Basel Assessment scale and Self-rating Anxiety Scale between the intervention group and the control group (P < .05). Conclusion. Mobile health intervention tools can provide efficient, comprehensive and accurate remote health intervention and professional support for patients, optimize the medical service system, and meet the social medical needs of high-quality nursing services. DOI: 10.52547/ijkd.7693